2015
DOI: 10.1016/j.jrmge.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin optical time-domain analysis for geotechnical monitoring

Abstract: In this paper, we show some recent experimental applications of Brillouin optical time-domain analysis (BOTDA) based sensors for geotechnical monitoring. In particular, how these sensors can be applied to detecting early movements of soil slopes by the direct embedding of suitable fiber cables in the ground is presented. Furthermore, the same technology can be used to realize innovative inclinometers, as well as smart foundation anchors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 2 publications
1
42
0
Order By: Relevance
“…This has a great deal of potential for geotechnical monitoring. A number of soil structures have been successfully monitored by DGM systems, such as slopes [2][3][4][5][6][7][8][9][10][11], foundations [12][13][14][15], and tunnels [16][17][18]. These systems have gained interest from researchers and engineers worldwide by their inherent advantages, including immunity to electromagnetic interference (EMI), high repeatability and durability, tiny size and light weigh, and the ability to multiplex many sensors on one single fiber.…”
Section: Introductionmentioning
confidence: 99%
“…This has a great deal of potential for geotechnical monitoring. A number of soil structures have been successfully monitored by DGM systems, such as slopes [2][3][4][5][6][7][8][9][10][11], foundations [12][13][14][15], and tunnels [16][17][18]. These systems have gained interest from researchers and engineers worldwide by their inherent advantages, including immunity to electromagnetic interference (EMI), high repeatability and durability, tiny size and light weigh, and the ability to multiplex many sensors on one single fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Installation of thousands of strain gauges along a single cable into the required earthwork structure can provide present situation of the ground which is highly informative [13]. Numerous researchers have practiced the usage of fiber optic strain sensors in the field of geotechnical engineering [14][15][16][17][18]. It has been identified that the Brillouin optical time-domain reflectometry (BOTDR) method is highly durable and a powerful fiber optic sensor which measures not only for health diagnosis but also in various engineering sectors for long distance and measures accurately with real-time data based system [19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…However, these conventional inclinometers have a number of disadvantages in practical applications, including low stability and durability, poor resistance to electromagnetic interference, high gravity dependence, and great signal loss for long-distance transmission. Recently, the fiber optic sensing technologies have been advocated for slope monitoring by some scholars [1][2][3][4][5][6][7][8]. Different types of FBG-based in-place inclinometers have been developed, which demonstrated various features, such as small size, superior chemical resistance and stability, immune to electro-magnetic interference, and quasi-distributed monitoring capability [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%